(untitled) (World Science, 2020)
According to the General Prosecutor’s Office, in 2019-2020 in Ukraine, the total number of crimes decreased, but at the same time the number of some grave and especially grave ones increased, for which prison terms are provided up to life imprisonment. Law enforcers also note an increase in juvenile delinquency with a tendency to particular cruelty. Obviously, the types of these serious crimes are associated with the level of the general index of aggression of offenders. Considering, also, the high rate of relapse of crimes related to aggressive behavior, we should talk about the special relevance and acuteness of this socio-psychological problem. In the article, the authors cite research data on the legalization of aggressiveness, taking into account the individual psychological characteristics of the individual and mesofactors: joint physical culture and sports activities at the level of a close social environment. An analysis of the results of the study indicates that the main group of students engaged in physical education and sports sections during 4 years of study at a university demonstrates significantly lower indicators of psychological and psychological characteristics indicating potential aggressiveness than the control group of students who did not engage in physical education / sports during the specified period.